2022
DOI: 10.1002/acr.24636
|View full text |Cite
|
Sign up to set email alerts
|

“Like Peanut Butter and Jelly”: A Qualitative Study of Chiropractic Care and Home Exercise Among Older Adults With Spinal Disability

Abstract: Objective. A mixed-methods, randomized controlled trial comparing short-and long-term chiropractic care and exercise therapy for spinal disability in older adults found no between-group differences in the primary outcome. However, those who received long-term management reported greater improvement in neck pain, self-efficacy, function, and balance. This nested qualitative study explored participants' perceptions of the benefits and drawbacks of chiropractic care and exercise for spine-related outcomes, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…(p. 97). Patients also confirmed the importance of this notion of change [39]: "The only thing that would really make it [treatment] worthwhile is if I felt comforted from it, or I had a slight glimmer of hope that there's going to be improvement. Otherwise, I don't see the purpose in it" (p. 11).…”
Section: Chiropractic Care As a Change Processmentioning
confidence: 87%
See 1 more Smart Citation
“…(p. 97). Patients also confirmed the importance of this notion of change [39]: "The only thing that would really make it [treatment] worthwhile is if I felt comforted from it, or I had a slight glimmer of hope that there's going to be improvement. Otherwise, I don't see the purpose in it" (p. 11).…”
Section: Chiropractic Care As a Change Processmentioning
confidence: 87%
“…Otherwise, I don't see the purpose in it" (p. 11). Patients also noted that their idea of the change they desire to see is individual and subjective [39]: as one participant emphasised "every patient here has their own story, so what is good for one person may not be good for another person. " (p. 6).…”
Section: Chiropractic Care As a Change Processmentioning
confidence: 99%
“…Relying solely on pharmacological therapy for cLBP is a hasty and ineffective approach [ 43 , 44 , 45 ]. Furthermore, in the therapeutic process, it is beneficial to involve professionals who specialize in the treatment of low back pain within an integrative medicine framework [ 46 ].…”
Section: Perspectivesmentioning
confidence: 99%
“…19 Although there were no between-group differences in back-and neck-related disability at 36 weeks, those in the 36-week treatment group reported greater improvement in self-efficacy at weeks 36 and 52, with objective improvement in functional ability and balance post-intervention. 20 Qualitative interviews embedded in the RCT revealed that participants experienced greater self-efficacy as a result of study treatments and valued improvement in functional ability when determining whether treatment was worthwhile. 20 It is unknown to what degree psychosocial measures, including self-efficacy and kinesiophobia, are associated with response to spinal manipulation and exercise among older adults with chronic spinal pain and disability.…”
mentioning
confidence: 99%
“…20 Qualitative interviews embedded in the RCT revealed that participants experienced greater self-efficacy as a result of study treatments and valued improvement in functional ability when determining whether treatment was worthwhile. 20 It is unknown to what degree psychosocial measures, including self-efficacy and kinesiophobia, are associated with response to spinal manipulation and exercise among older adults with chronic spinal pain and disability. Understanding the impact of non-pharmacological treatments on improving self-efficacy and reducing kinesiophobia and how these are associated with reductions in spine-related disability could support spine care in older adults and help identify individuals most likely to respond to treatment.…”
mentioning
confidence: 99%